2024
DOI: 10.3389/fnut.2023.1215212
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and age-related cataract: an updated systematic review and dose–response meta-analysis of prospective cohort studies

Sana Niazi,
Majid Moshirfar,
Mohammad H. Dastjerdi
et al.

Abstract: ObjectiveThere are inconsistent findings on the association between obesity and age-related cataract (ARC). This systematic review was done to summarize available findings on the association between obesity [defined by body mass index (BMI)] and ARC by performing a dose–response meta-analysis on eligible prospective cohort studies.MethodsWe performed a systematic search in PubMed, Scopus, ISI Web of Knowledge, and Google Scholar until June 2022 to identify eligible publications.ResultsIn total, 16 studies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Interestingly, an updated systematic review and metaanalysis revealed an association between obesity (defined by BMI) and increased risk of SC, posterior subcapsular cataract (PSC), and cortical cataract in adults. Nevertheless, such a positive association did not exist for nuclear cataract [41] . Previous studies have also investigated the genetic association of the obesity gene SNP with SC.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, an updated systematic review and metaanalysis revealed an association between obesity (defined by BMI) and increased risk of SC, posterior subcapsular cataract (PSC), and cortical cataract in adults. Nevertheless, such a positive association did not exist for nuclear cataract [41] . Previous studies have also investigated the genetic association of the obesity gene SNP with SC.…”
Section: Discussionmentioning
confidence: 81%
“…In conclusion, there is evidence from the literature that obesity, defined by BMI, is associated with an increased risk of age-related cataracts and posterior subcapsular and cortical cataracts in adults [ 28 ].…”
Section: Obesity and Eye Diseasesmentioning
confidence: 99%
“…At a systemic level, higher BMI is linked to a greater risk of type 2 diabetes, cardiovascular diseases, and sleep apnea ( 7 , 8 ). Locally, when focusing on the eyes, higher BMI is also significantly associated with age-related cataracts, age-related macular degeneration, and diabetic retinopathy ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%